2018
DOI: 10.1080/09712119.2018.1481855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary β-glucan supplementation on growth performance, nutrient digestibility, and characteristics of feces in weaned pigs

Abstract: A total of 150 crossbred weaned pigs [(Yorkshire × Landrace) × Duroc] with an average body weight of 6.75 ± 0.49 kg were used in a 6-wk trial to determine the effects of dietary supplementation of β-glucan on growth performance, nutrient digestibility, and characteristics of feces (fecal score, microbiota, moisture, and pH) in weaned pigs. The corn-soybean meal based dietary treatments included: 1) antibiotic (30 ppm Tiamulin), 2) 0% β-glucan, 3) 0.1% β-glucan, 4) 0.2% β-glucan, and 5) 0.4% β-glucan. Dietary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…This finding is in agreement with that of Tuoi et al [10], who observed that inclusion of combinations of 1.0 g/kg β-glucan and MOS in the piglet diet markedly increased the abundance of Lactobacillus spp. However, this contrasted with a previous report in which an increase in intestinal microbiota was not observed [34]. These inconsistent results may be due to the different inclusion levels, dietary compositions, or HY purity utilized.…”
Section: Fecal Microbial Sheddingcontrasting
confidence: 99%
“…This finding is in agreement with that of Tuoi et al [10], who observed that inclusion of combinations of 1.0 g/kg β-glucan and MOS in the piglet diet markedly increased the abundance of Lactobacillus spp. However, this contrasted with a previous report in which an increase in intestinal microbiota was not observed [34]. These inconsistent results may be due to the different inclusion levels, dietary compositions, or HY purity utilized.…”
Section: Fecal Microbial Sheddingcontrasting
confidence: 99%
“…Each pen, housing 6 piglets of 3 barrows and 3 gilts, represented an experimental unit. The dietary inclusion at the level of 0.75% for the three prebiotics and the oat b-glucan in the experimental diets were to reflect the ranges of their dietary supplementation levels reported in the current literature (Mair et al, 2010;Park et al, 2018;Xing et al, 2018;Uerlings et al, 2021) in hopefully eliciting positive changes in growth performance, nutrition and and/or physiological endpoints while also being economically feasible for the industry should commercial applications of these potential gut modifiers as feed additives be attempted.…”
Section: Experimental Diets and Designmentioning
confidence: 99%
“…In agreement with our findings, later work done by Hiss and Sauerwein (2003) who found that supplementing up to 0.03% of yeast-derived b-(1-3/1-6)-glucan had a trend to increase ADFI but did not improve ADG in the weanling pigs. Hahn et al (2006) in supplementing up to 0.04% bglucan and Park et al (2018) in supplementing up to 0.40% bglucan did not report consistent improvements in performances in weanling pigs. In a recent study by Wu et al (2021), dietary supplementation (at 0.02%) of b-glucan of bacterial origin could improve gut morphology, biochemical and microbiome endpoints with improvement in ADG but not ADFI and F:G ratio in weanling pigs.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, yeast β-glucans provide a valuable tool to the ruminant producer as an alternative to antibiotics (Dina and Mariët, 2018). β-glucan from rice bran could have alternative antibiotic effects and improve productivity of weaned pigs (Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%